MIS-TLIF for a gas-containing discal cyst with adjacent -lumbar spondylolisthesis: a case report and literature review - Huang, Haoyun; Li, Guangye; Deng, Junwen; Chen, Rigao; Zhou, Yi (Frontiers in Surgery, 2025)
IntroductionGas-containing lumbar disc cysts are a rare cause of neurogenic pain. These cysts typically occur in middle-aged and elderly patients and are predominantly associated with lumbar disc degeneration, presenting with sensory and motor deficits in the affected dermatomes. The prevalence remains unclear due to the limited number of reported cases. Instances involving concomitant lumbar spondylolisthesis at adjacent segments are extremely rare and poorly documented in the current literature.Case presentationThe 67-year-old woman presenting with recurrent lower back pain, numbness, and swelling in the left lower limb for over 6 months. Previous conservative treatments yielded minimal relief. DR imaging showed anterior displacement of the L4 vertebral body and reduced L5/S1 intervertebral height. CT imaging confirmed L4 anterior slippage with L4/5 segmental spinal stenosis, a disc vacuum phenomenon at L5/S1, and a gas-containing cyst at the left posterior margin of the intervertebral disc. MRI imaging revealed a low-signal area on T1-weighted imaging/T2-weighted imaging sequences at the cyst location. A preliminary diagnosis of L5/S1 gas-containing disc cyst with adjacent L4/5 spondylolisthesis was established based on comprehensive clinical assessments. And a two-segment minimally invasive transforaminal lumbar interbody fusion was performed at L4/5 and L5/S1.ResultThe patient experienced significant symptom relief, with postoperative CT confirming cyst resolution, restored L5/S1 intervertebral height, and L4/5 stability. At 1-month follow-up, the patient reported minimal pain. By 3 months, lower extremity symptoms had fully resolved.ConclusionThese findings suggest that fusion surgery might be a superior treatment option for cases involving discal cysts with spondylolisthesis, particularly when clinical evidence of vertebral instability is present.